2016
DOI: 10.1111/avsc.12243
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use history exerts long‐term effects on the clear‐cut flora in boreonemoral Sweden

Abstract: Questions: Can signs of 19th century grassland management, which can be observed in the flora immediately (2-4 yrs) after clear-cutting in boreonemoral Sweden, still remain 4 yrs later? Do the effects from the time since clear-cutting differ between forest and grassland plant species?Location: Province of € Osterg€ otland, southern Sweden.Methods: Twelve contemporary clear-cut areas that were once meadows and 12 that were once forests were selected using land-use maps from the 1870s. Grasses and herbaceous pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
1
19
2
Order By: Relevance
“…Across both land-use intensities, the intensively managed plots have become more similar over time, while this was not the case for the group of less intensively managed plots, where communities on former infield and outland were still very distinct from each other in 2014. These findings contrast with those of Jonason, Bergman, Westerberg, and Milberg (2016), who observed that clear-cutting sustained legacies from former use as meadowland. However, they observed only small differences in soil nutrients between land-use types (i.e., forest history vs. meadow history), while soil nutrient content was an important driver behind land-use legacies (resulting from infield vs. outland use) in our study.…”
Section: Research Question 2: Impact Of Recent Management On the Uncontrasting
confidence: 99%
“…Across both land-use intensities, the intensively managed plots have become more similar over time, while this was not the case for the group of less intensively managed plots, where communities on former infield and outland were still very distinct from each other in 2014. These findings contrast with those of Jonason, Bergman, Westerberg, and Milberg (2016), who observed that clear-cutting sustained legacies from former use as meadowland. However, they observed only small differences in soil nutrients between land-use types (i.e., forest history vs. meadow history), while soil nutrient content was an important driver behind land-use legacies (resulting from infield vs. outland use) in our study.…”
Section: Research Question 2: Impact Of Recent Management On the Uncontrasting
confidence: 99%
“…In grassland systems, time lags in the order of a century have been documented Eriksson 2004, Helm et al 2006) and legacies of previous grassland management in what is currently forest and maintained over a century, have been documented (Herben et al 2006, Johansson et al 2011). These legacies may also remain after one forest-cycle of clear-cutting (Jonason et al 2016). Very few similar studies have been conducted in forest systems and focusing on what is regarded as forest species, perhaps due to a preconceived notion that such legacies are not expected when research is conducted in forests.…”
Section: Biological Cultural Traces In Forestsmentioning
confidence: 99%
“…It is worth noting that the positive value of forest on butterflies may not be persistent over time. Jonason et al (2014Jonason et al ( , 2016 showed that plant species richness in clear-cuts was related to historical land use in the 1800 s and the introduction of modern forest management practices will create more uniform, evenaged, dense and dark stands hostile to grassland plants (Niklasson and Granström 2000;Axelsson and Ö stlund 2001;Bergstedt et al 2017). Hence, we expect that future forests will contain fewer open areas, and clear-cuts will become less rich in plants useful for butterflies.…”
Section: Butterfly Richnessmentioning
confidence: 99%